Milner and the mind of imperialism - Van Helten, Jean Jacques (My University, 1979)
Capitalist development in Southern Africa, particularly in Kimberley and on the Rand, was very much the result of the penetration of British and foreign capital as well ac the rapid growth of commercial interests. The continued expansion of the mining industry, with its huge amounts of initial capital outlay, particularly after 1893 when the deep levels came into operation, depended upon the state of the capital markets of Europe: speculative booms in "kaffir" shares not only lined the pockets of investors but also provided new working capital, for little capital was raised by the issue of debentures, (l).
African Studies Seminar series. Paper presented 26 February 1979
Keywords: Imperialism. South Africa; Capitalism. South Africa